Consciousness, Theatre, Literature and the Arts 2013. - Meyer-Dinkgräfe, Daniel, 1958- (Cambridge Scholars Publishing, 2014)
The essays collected in this volume were initially presented at the Fifth International Conference on Consciousness, Theatre, Literature and the Arts, held at the University of Lincoln, June 15-17, 2013. The conference was organised on the basis of the success of its predecessors in 2005, 2007, 2009 and 2011, and on the basis of the success of the Rodopi book series Consciousness, Literature and the Arts, which has to date seen 34 volumes in print, with another 12 in press or in the process o ...